Beauty : Singular ~ Plural. - Coirier, Lise; Coudyzer, Eva; Elias, Willem; De Vooght, Gino; Aelbrecht, Evelyne; Smets, Francis; Valcke, Johan; Triënnale voor Vormgeving / Design Triennial Brussel 2007 (Oostkamp : Stichting Kunstboek, 2007)
Aerts, Leo ; Allaeys, Philippe ; Beernaert, Roel ; Berteau, Alain ; Bihr, Damien ; Casimir ; De Pelsmacker, Hans ; De Rudder, Nora ; Dessauvage, Tjok ; Destino, Nicolas ; Dewez, Nathalie ; El-Asmar, Nedda ; Hermans, Linda ; Huycke, David ; Lanckman, An ; et al.
Koninklijke Musea voor Kunst en Geschiedenis, Brussel, 14/12/2007 - 02/03/2008 / 5e Triënnale voor Vormgeving/design
kunstcatalogus